Fluid Nest Membership Drives Variable Relatedness in Groups of a Facultatively Social Bee - Ostwald, Madeleine M.; Dahan, Romain A.; Shaffer, Zachary; Fewell, Jennifer H. (Frontiers in Ecology and Evolution, 2021)
Kin selection theory has dominated our understanding of the evolution of group living. However, many animal groups form among non-relatives, which gain no indirect fitness benefits from cooperating with nestmates. In this study, we characterized the relatedness and inter-nest migration behavior of the facultatively social carpenter bee, Xylocopa sonorina. Nesting constraints due to costly nest construction in this species give rise to intense intraspecific competition over access to existing nests. We used mark-recapture techniques to characterize patterns of dispersal and nest relocation within a nesting aggregation of spatially clustered nests. Two-thirds of bees relocated at least once during the reproductive season, likely to seek reproductive opportunities in another nest. This fluid nest membership creates opportunities for association among non-relatives. To assess the effects of this dynamic nesting behavior on group relatedness, we used microsatellite analysis to estimate relative relatedness within and between nests in the aggregation. We found that relatedness was variable across sampling years, but that in many cases nestmates were no more related to one another than they were to non-nestmate bees in the population. Together, these results suggest that group composition in X. sonorina may result from strategies to maximize direct fitness. This study supports the hypothesis that factors beyond kinship, such as ecological constraints, are likely to drive group formation in this species.